Hospital managers’ opinions on social supervisory boards and supervisory boards - Kautsch, Marcin (Journal of Public Governance, 2015)
The paper presents the results of research on the opinions of hospital managers concerning the operation and usefulness of social supervisory boards and supervisory boards. The results of the research suggest that supervisory boards are useful for hospitals and their owners. Social supervisory boards are more beneficial to the owners. The impact of supervisory boards on economic and management issues is particularly important. The boards themselves operate without significant problems. Respondents stress, however, that board members are not always prepared for meetings and do not always have appropriate qualifications. Hospital managers appreciate the contribution of supervisory boards much more than that of social supervisory boards.